Rice Fertilization-Independent Endosperm1 Regulates Seed Size under Heat Stress by Controlling Early Endosperm Development. Issue 1 (3rd March 2014) - Folsom, Jing J.; Begcy, Kevin; Hao, Xiaojuan; Wang, Dong; Walia, Harkamal
Abstract : Early seed development in rice is highly sensitive to heat stress and negatively affects seed enlargement because of epigenetic misregulation of endosperm development . Abstract: Although heat stress reduces seed size in rice ( Oryza sativa ), little is known about the molecular mechanisms underlying the observed reduction in seed size and yield. To elucidate the mechanistic basis of heat sensitivity and reduced seed size, we imposed a moderate (34°C) and a high (42°C) heat stress treatment on developing rice seeds during the postfertilization stage. Both stress treatments reduced the final seed size. At a cellular level, the moderate heat stress resulted in precocious endosperm cellularization, whereas severe heat-stressed seeds failed to cellularize. Initiation of endosperm cellularization is a critical developmental transition required for normal seed development, and it is controlled by Polycomb Repressive Complex2 (PRC2) in Arabidopsis ( Arabidopsis thaliana ). We observed that a member of PRC2 called Fertilization-Independent Endosperm1 ( OsFIE1 ) was sensitive to temperature changes, and its expression was negatively correlated with the duration of the syncytial stage during heat stress. Seeds from plants overexpressing OsFIE1 had reduced seed size and exhibited precocious cellularization. The DNA methylation status and a repressive histone modification of OsFIE1 were observed to be temperature sensitive. Our data suggested that the thermal sensitivity of seed enlargement could partly be caused by altered epigenetic regulation of endosperm development during the transition from the syncytial to the cellularized state.